Risk-benefit balance assessment of SSRI antidepressant use during pregnancy and lactation based on best available evidence. (March 2015) - Weisskopf, Etienne; Fischer, Céline J; Bickle Graz, Myriam; Morisod Harari, Mathilde; Tolsa, Jean-François; Claris, Olivier; Vial, Yvan; Eap, Chin B; Csajka, Chantal; Panchaud, Alice
<x xml:space="preserve">Abstract</x> Introduction: Psychiatric disorders are among the leading causes of disability in Western societies. Selective serotonin reuptake inhibitors (SSRIs) are the most frequently prescribed antidepressant drugs during pregnancy and the postpartum period. Over the last decade, conflicting findings regarding the safety of SSRI drugs during pregnancy and lactation have questioned whether such treatments should be used during this period. Areas covered: We discuss the main criteria that should be considered in the risk/benefit assessment of SSRI treatment in pregnant and/or breastfeeding patients (i.e., risks associated with SSRI use and with untreated depression as well as therapeutic benefits of SSRI and some alternative treatment strategies). For each criterion, available evidence has been synthesized and stratified by methodological quality as well as discussed for clinical impact. Expert opinion: Currently, it is impossible for most of the evaluated outcomes to distinguish between the effects related to the mother's underlying disease and those inherent to SSRI treatment. In women suffering from major depression and responding to a pharmacological treatment, introduction or continuation of an SSRI should be encouraged in order to prevent maternal complications and to preserve maternal–infant bonding. The choice of the right drug depends above all on individual patient characteristics such as prior treatment response, diagnoses and comorbid conditions.